LEBIH DARI SEKEDAR MENUTUP AURAT: MEMBEDAH EKOSISTEM HALAL DALAM INDUSTRI FESYEN MODERN - Sonalia Sonalia; Ujang Ujang; Lisnawati Lisnawati (JURNAL ILMIAH NUSANTARA, 2026)
This research explores the dynamics of halal fashion, which has transformed from a religious obligation into a modern lifestyle phenomenon within the global creative industry. The primary objective of this study is to define the comprehensive boundaries of halal fashion, analyze the driving factors behind the modest fashion trend, and evaluate the role of halal certification in ensuring product integrity in the global market. The method employed is a qualitative descriptive analysis with a literature review on Sharia principles, halal product guarantee regulations, and contemporary market trends. Research findings indicate that halal fashion integrates five core principles covering the aurat, loose-fitting, non-transparent, avoiding tabarruj, and sincere intention which now collaborate with modern aesthetics such as hijab street style. Halal certification through Law No. 33 of 2014 has proven crucial in building consumer trust (peace of mind) through supply chain transparency that is clean from upstream to downstream. The implications of this research confirm that effective marketing strategies must integrate Islamic ethical values with the sustainable fashion movement and digital ecosystem optimization. Halal fashion is not only a symbol of piety but also represents inclusive, transparent, and competitive universal quality excellence on the international stage.